Preparation of acid-base synergistic catalyst and application thereof in catalytic preparation of lactide from lactic acid by one-step gas phase method

The synthesis of lactic acid from lactate in a one-step gas-phase process using an acid-base synergistic catalyst supported by SBA-15 solves the problems of length and high cost of the traditional two-step method, achieving highly selective and high-yield lactide synthesis, which is suitable for the industrial production of biodegradable materials.

CN118751274BActive Publication Date: 2025-11-28CHINA UNIV OF PETROLEUM (EAST CHINA) +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410751105.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-11-28
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

In the existing technology, the traditional two-step synthesis of lactide is lengthy, has high equipment requirements, high cost, low optical purity, and low raw material utilization. Furthermore, existing catalysts are easily corroded by lactic acid or have conversion equilibrium limitations.

Method used

An SBA-15 supported acid-base synergistic catalyst was used to catalyze the synthesis of lactic acid into lactide in a one-step gas-phase process by utilizing the synergistic effect of the catalyst. Water was removed by a flash evaporation device to promote the forward reaction and reduce side reactions.

Benefits of technology

It improves the selectivity and yield of lactide, reduces production costs, and has good catalyst stability, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005622426940000041
    Figure GDA0005622426940000041
  • Figure HDA0005622426950000011
    Figure HDA0005622426950000011
  • Figure HDA0005622426950000012
    Figure HDA0005622426950000012
Patent Text Reader

Abstract

The application belongs to the technical field of chemical synthesis, and relates to preparation of an acid-base synergistic catalyst and application of the acid-base synergistic catalyst in catalysis of synthesis of lactide from lactic acid in a one-step gas phase method. The acid-base synergistic catalyst is characterized in that SBA-15 with a large specific surface area is synthesized as a catalyst carrier, an alkaline active component is introduced by an in-situ method, and an alkaline catalyst is prepared. Then, an acidic component is introduced into the above catalyst by an impregnation method, so as to obtain an SBA-15-loaded acid-base synergistic catalyst. The acid-base synergistic catalyst is innovatively used for synthesis of lactide from lactic acid in a one-step gas phase method. Compared with a single acid-base component, the acid-base synergistic catalyst can not only obtain lactide with high optical purity, but also reduce the purification difficulty of the lactide. Moreover, the one-step gas phase method is operated at normal pressure, the production condition is mild, the production cost is reduced, and the acid-base synergistic catalyst has a large industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of biodegradable material synthesis, and particularly relates to preparation of an SBA-15 loaded acid-base synergistic catalyst and application of the catalyst in catalyzing synthesis of lactide from lactic acid in a one-step gas phase method. BACKGROUND

[0002] With the rapid development of global economy, people's awareness of environmental protection is gradually enhanced. The non-degradability of traditional petroleum-based materials and the increasing shortage of fossil energy, finding green energy to replace petroleum to alleviate the problem of resource shortage and environmental pollution. In recent years, the research and production of completely biodegradable materials such as polylactic acid (PLA) have become a hot topic in academia and industrial production. PLA has the advantages of wide range of production raw materials, complete biodegradability, low carbon emission and good biocompatibility, and is the most potential and popular biodegradable material at present, which is widely used in biomedical, agricultural production, catering and other industries.

[0003] Two-step method is used in industry to produce polylactic acid. First, L-lactic acid (D-lactic acid) is synthesized into L-lactide (D-lactide) under high temperature and vacuum, and then the lactide is synthesized into PLA by ring-opening polymerization under the action of catalyst. In these steps, the main factor limiting the application range and market competitiveness of PLA is the optical purity of lactide. At present, two-step method is used in industry to synthesize lactide. First, lactic acid is dehydrated and condensed to form lactic acid oligomer under high temperature and vacuum; second, lactic acid oligomer is depolymerized and cyclized to form crude lactide under high temperature, vacuum and catalyst, and then high optical purity lactide is obtained by separation and purification. For example, Chinese invention patent CN102675277A uses zinc oxide and stannous octoate as catalyst, and sodium dodecyl sulfonate as surfactant, to obtain 83-91% crude lactide yield under high temperature (165-200℃) and low pressure (0.08-0.09MPa). Although the two-step method is mature, it has the problems of long route, many operation units, high requirement for equipment in high temperature and vacuum environment, high operation cost, low raw material utilization rate and low optical purity of product.

[0004] To solve the problems related to the two-step method, research has shifted to the one-step ring-opening dehydration synthesis of lactide from lactic acid. The invention patent CN108610323A uses H-Beta as a catalyst to synthesize optically pure lactide with a purity of >96% at 50-1500 Pa and 120-150°C, overcoming some of the shortcomings of the two-step synthesis of lactide. However, the aluminum element in the silicon-aluminum H-Beta is easily eroded by lactic acid, causing the collapse of the molecular sieve framework structure. CN112028869A discloses a catalyst containing tin-containing silicon-aluminum molecular sieve and lactic acid ester as raw material, which can obtain a selectivity of L-lactide of more than 92%. However, the condensation of lactic acid ester and the depolymerization of lactide are reversible processes, which are limited by the conversion equilibrium. CN108424408A uses tin or zinc catalysts to obtain a lactide yield of more than 90% and an optical purity of more than 90%, solving the problems of lactide yield and optical purity. However, separation and purification are required, increasing production costs. SUMMARY

[0005] To solve the problems in the prior art, the present application provides a preparation method of an SBA-15 loaded acid-base synergistic catalyst and its application in the one-step gas-phase synthesis of lactide from lactic acid. The acid-base synergistic effect of the catalyst is used to achieve efficient synthesis of lactide, and the flash device is used to achieve water removal, promoting the forward progress of the reaction and reducing the occurrence of side reactions, with a maximum L-lactide selectivity of 96%.

[0006] To achieve the above-mentioned purposes, the technical scheme adopted by the present application is as follows:

[0007] A preparation method of an SBA-15 loaded acid-base synergistic catalyst, specifically comprising the following steps:

[0008] Preparation of the SBA-15 loaded single base component catalyst:

[0009] (1) Dissolve 2-4 g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) in 75-150 g of 1.60 mol / L hydrochloric acid solution, and stir at 400-1000 r / min at room temperature;

[0010] (2) Add 4.25-8.50 g of tetraethyl orthosilicate (TEOS) to the solution of step (1) and stir at 400-1000 r / min at room temperature;

[0011] (3) Add different amounts of base component precursor to the solution of step (2) and stir at 40°C, 400-1000 r / min for 12-48 h;

[0012] (4) transferring the mixture in step (3) into a crystallization kettle with a polytetrafluoroethylene lining, and crystallizing at 80-160℃ for 24-48h;

[0013] (5) drying the filter cake obtained after washing the mixture obtained in step (4) with deionized water for multiple times at 100℃ for 24h;

[0014] (6) placing the substance obtained in step (5) into a muffle furnace, and calcining at 2℃ / min to 550℃ for 6h to obtain the SBA-15 loaded single base component catalyst.

[0015] The preparation of the SBA-15 loaded acid-base synergistic catalyst, and the loading amount is 10-30wt% calculated by the active metal.

[0016] 1) dissolving a certain amount of the acid component in 50-100g of deionized water to obtain an acid component solution with different mass fractions;

[0017] 2) adding a certain amount of the SBA-15 loaded single base component catalyst into the salt solution obtained in step 1) and stirring at 40-70℃ for 1-4h;

[0018] 3) drying the filter cake obtained after filtering and washing the mixture obtained in step 2) for multiple times in an oven at 80℃ for 12-48h;

[0019] 4) placing the substance obtained in step 3) into a muffle furnace, and calcining at 2℃ / min to 550℃ for 3h to obtain the SBA-15 loaded acid-base synergistic catalyst.

[0020] The precursor of the acid component is one of (CH3COO)2Zn, ZrSO4, AlCl3 and the like; and the precursor of the base component is one of (CH3COO)2Mg, BaCl2;

[0021] The application of the catalyst, and the application of the catalyst in the gas phase one-step synthesis of lactide from lactic acid.

[0022] A method for the gas phase one-step synthesis of lactide from lactic acid, which uses L-lactic acid (D-lactic acid) as the raw material and the SBA-15 loaded acid-base synergistic component as the catalyst, and the mass space velocity is 1-5h -1 , the gasification temperature is 140-160℃, and the reaction temperature is 210-250℃, so that lactic acid is efficiently converted into lactide.

[0023] The present application has the following advantages:

[0024] The SBA-15 with large specific surface area is used as the carrier in the application, the active component is uniformly dispersed in the carrier and has good stability, and the industrial application prospect is wide. The used acid and base component precursors are low in price, and the production cost is low. Meanwhile, the water generated in the reaction is discharged in time by using a flash device, the balance is broken, the reaction is promoted in the positive direction, the occurrence of side reactions is reduced, and the conversion rate and lactide yield are improved. BRIEF DESCRIPTION OF DRAWINGS

[0025] Figure 1 The XRD pattern of the SBA-15 supported acid-base synergistic catalyst MgO-ZnO / SBA-15 prepared in the application.

[0026] Figure 2 The XRD pattern of the SBA-15 supported acid-base synergistic catalyst BaO-ZnO / SBA-15 prepared in the application.

[0027] Figure 3 The adsorption isotherm and pore size distribution of the SBA-15 supported acid-base synergistic catalyst MgO-ZnO / SBA-15 and BaO-ZnO / SBA-15 prepared in the application.

[0028] Figure 4 The device used in the application. DETAILED DESCRIPTION

[0029] In order to more clearly illustrate the application, the following examples are listed, but are not limited thereto.

[0030] Example 1

[0031] (1) Preparation of SBA-15 in situ supported single base component magnesium oxide MgO / SBA-15

[0032] 2.0g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) was dissolved in 75.0g of 1.60mol / L hydrochloric acid solution, and the solution was stirred at 800r / min at room temperature; then 22.78g of magnesium acetate was added to the above solution and stirred to dissolve at room temperature; then 4.25g of tetraethyl orthosilicate (TEOS) was added to the above solution, and the solution was stirred at 800r / min at 40℃ for 24h to form a homogeneous solution; then the above mixture was transferred to a crystallization kettle with a polytetrafluoroethylene lining, and crystallization was carried out at 100℃ for 24h; then the obtained mixture was washed with deionized water for several times, and the filter cake obtained after drying at 100℃ for 24h; then the obtained powder was placed in a muffle furnace, and the temperature was increased to 550℃ at a rate of 2℃ / min, and calcination was carried out for 6h to obtain the SBA-15 supported single base component magnesium oxide MgO / SBA-15 catalyst.

[0033] (2) Preparation of SBA-15 supported acid-base synergistic catalyst MgO-ZnO / SBA-15

[0034] 3.06 g of zinc acetate was added to 27.0 g of deionized water to prepare a 10 wt% zinc acetate solution; then 0.40 g of MgO / SBA-15 was added to the above solution and stirred at 60 °C for 2 h; the above solution was filtered and washed several times and the filter cake was dried in an oven at 80 °C for 24 h; then the obtained powder was placed in a muffle furnace and calcined at 550 °C for 3 h at a rate of 2 °C / min to obtain the SBA-15 supported acid-base synergistic catalyst MgO-ZnO / SBA-15.

[0035] Figure 1 Its XRD pattern, by Figure 1 It can be seen that the synthesized SBA-15 supported acid-base synergistic catalyst MgO-ZnO / SBA-15 still has the characteristic peaks of SBA-15. Figure 3 Its N2 physical adsorption diagram, as shown in Table 1, indicates a specific surface area of ​​620 m². 2 / g.

[0036] Table 1

[0037]

[0038] Example 2

[0039] (1) Preparation of SBA-15 with in-situ supported single alkali component barium oxide (BaO) / SBA-15

[0040] 2.0 g of poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer (P123) was dissolved in 75.0 g of 1.60 mol / L hydrochloric acid solution and stirred at 800 r / min at room temperature. Then, 25.86 g of barium chloride was added to the solution and stirred at room temperature. Next, 4.25 g of tetraethyl orthosilicate (TEOS) was added to the solution and stirred at 800 r / min at 40 °C for 24 h to form a homogeneous solution. The mixture was then transferred to a crystallization vessel lined with polytetrafluoroethylene and crystallized at 100 °C for 24 h. The resulting mixture was then washed multiple times with deionized water, and the resulting filter cake was dried at 100 °C for 24 h. Finally, the resulting powder was placed in a muffle furnace and calcined at 550 °C at a rate of 2 °C / min for 6 h to obtain the SBA-15 supported single-base component barium oxide (BaO) / SBA-15 catalyst.

[0041] (2) Preparation of SBA-15 supported acid-base synergistic catalyst BaO-ZnO / SBA-15

[0042] 3.06 g of zinc acetate was added to 27.0 g of deionized water to prepare a 10 wt% zinc acetate solution; then 0.40 g of BaO / SBA-15 was added to the above solution and stirred at 60 °C for 2 h; the above solution was filtered and washed several times and the filter cake was dried in an oven at 80 °C for 24 h; then the obtained powder was placed in a muffle furnace and calcined at 550 °C for 3 h at a temperature of 2 °C / min to obtain the SBA-15 supported acid-base synergistic catalyst BaO-ZnO / SBA-15.

[0043] Figure 2 Its XRD pattern, by Figure 1 It can be seen that the synthesized SBA-15 supported acid-base synergistic catalyst BaO-ZnO / SBA-15 still has the characteristic peaks of SBA-15. Figure 3 Its N2 physical adsorption diagram, as shown in Table 1, indicates a specific surface area of ​​586 m². 2 / g.

[0044] Example 3

[0045] Weigh 0.50 g of the MgO / SBA-15 catalyst from Example 1 and place it in a fixed-bed reactor. The lactic acid is 50 wt% L-lactic acid, and the mass hourly space velocity (WHSV) is 1 h⁻¹. -1 The vaporization temperature is 150℃, the reaction temperature is 210℃, and the selectivity of L-lactide is 72%.

[0046] Example 4

[0047] Weigh 0.50 g of the MgO / SBA-15 catalyst from Example 1 and place it in a fixed-bed reactor. The lactic acid is 50 wt% L-lactic acid, and the mass hourly space velocity (WHSV) is 1 h⁻¹. -1 The vaporization temperature is 150℃, the reaction temperature is 230℃, and the selectivity of L-lactide is 83%.

[0048] Example 5

[0049] Weigh 0.50 g of the MgO / SBA-15 catalyst from Example 1 and place it in a fixed-bed reactor. The lactic acid is 50 wt% L-lactic acid, and the mass hourly space velocity (WHSV) is 1 h⁻¹. -1 The vaporization temperature is 150℃, the reaction temperature is 250℃, and the selectivity of L-lactide is 76%.

[0050] Example 6

[0051] Weigh 0.50 g of the MgO / SBA-15 catalyst from Example 1 and place it in a fixed-bed reactor. The lactic acid is 50 wt% L-lactic acid, and the mass hourly space velocity (WHSV) is 5 h⁻¹. -1 The vaporization temperature is 150℃, the reaction temperature is 230℃, and the selectivity of L-lactide is 64%.

[0052] Example 7

[0053] Weigh 0.50 g of the MgO-ZnO / SBA-15 catalyst from Example 1 and place it in a fixed-bed reactor. The lactic acid is 50 wt% L-lactic acid, and the mass hourly space velocity is 1 h⁻¹. -1 The vaporization temperature is 150℃, the reaction temperature is 230℃, and the selectivity of L-lactide is 96%.

[0054] Example 8

[0055] Weigh 0.50 g of the MgO-ZnO / SBA-15 catalyst from Example 1 and place it in a fixed-bed reactor. The lactic acid is 50 wt% L-lactic acid, and the mass hourly space velocity (WHSV) is 5 h⁻¹. -1 The vaporization temperature is 150℃, the reaction temperature is 230℃, and the selectivity of L-lactide is 85%.

[0056] Example 9

[0057] Weigh 0.50 g of the BaO / SBA-15 catalyst from Example 1 and place it in a fixed-bed reactor. The lactic acid is 50 wt% L-lactic acid, and the mass hourly space velocity (WHSV) is 1 h⁻¹. -1 The vaporization temperature is 150℃, the reaction temperature is 230℃, and the selectivity of L-lactide is 72%.

[0058] Example 10

[0059] Weigh 0.50 g of the BaO / SBA-15 catalyst from Example 1 and place it in a fixed-bed reactor. The lactic acid is 50 wt% L-lactic acid, and the mass hourly space velocity (WHSV) is 5 h⁻¹. -1 The vaporization temperature is 150℃, the reaction temperature is 230℃, and the selectivity of L-lactide is 63%.

[0060] Example 11

[0061] Weigh 0.5 g of the BaO-ZnO / SBA-15 catalyst from Example 1 and place it in a fixed-bed reactor. The lactic acid is 50 wt% L-lactic acid, and the mass hourly space velocity is 1 h⁻¹. -1 The vaporization temperature is 150℃, the reaction temperature is 230℃, and the selectivity of L-lactide is 88%.

[0062] Example 12

[0063] Weigh 0.50 g of the BaO-ZnO / SBA-15 catalyst from Example 1 and place it in a fixed-bed reactor. The lactic acid is 50 wt% L-lactic acid, and the mass hourly space velocity (WHSV) is 5 h⁻¹. -1 The vaporization temperature is 150℃, the reaction temperature is 230℃, and the selectivity of L-lactide is 74%.

[0064] From the above examples, it can be seen that the acid-base synergistic catalyst obtained by loading the acid and base components on the SBA-15 carrier with a large specific surface area increases the contact between the catalyst and the reaction substrate, thereby significantly improving the selectivity of L-lactide. If the temperature is too high, the lactide itself will racemize, resulting in a decrease in the selectivity of L-lactide. About 230°C is the optimal reaction temperature.

[0065] The above merely describes preferred embodiments of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. The application of an SBA-15 supported acid-base synergistic catalyst, characterized in that: The catalyst is used for the one-step gas-phase synthesis of lactide from lactic acid. The catalyst is synthesized by introducing a basic component in situ during the synthesis of the SBA-15 support with a large specific surface area, followed by introducing an acidic component via impregnation, thereby synthesizing an SBA-15-supported acid-base synergistic catalyst. The specific surface area of ​​the SBA-15-supported single basic component is 330-689 m². 2 / g; the precursors of the acidic components are (CH3COO)2Zn, ZrSO4, and AlCl3, and the precursors of the basic components are (CH3COO)2Mg and BaCl2.

2. The application according to claim 1, characterized in that: The steps for introducing alkaline components in situ are as follows: (1) Dissolve 2-4g of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123) in 75-150g of 1.60mol / L hydrochloric acid solution and stir at 400-1000r / min at room temperature; (2) Add 4.25 to 8.50 g of tetraethyl orthosilicate (TEOS) to the solution obtained in step (1) and stir at 400 to 1000 r / min at room temperature to dissolve it; (3) Add different masses of alkaline component precursors to the solution obtained in step (2) and stir at 40°C and 400-1000 r / min for 12-48 h; (4) Transfer the mixture obtained in step (3) to a crystallization vessel with a polytetrafluoroethylene liner and crystallize at 80-160°C for 24-48 hours; (5) The filter cake obtained by washing the mixture obtained in step (4) with deionized water multiple times is dried at 100°C for 24 hours. (6) The material obtained in step (5) is placed in a muffle furnace and calcined at 2℃ / min to 550℃ for 6h to obtain SBA-15 supported single alkaline component catalyst.

3. The application according to claim 2, characterized in that: The steps for introducing acidic components are as follows: 1) Dissolve a certain amount of acidic component precursor in 50-100g of deionized water to obtain acidic component precursor solutions with different mass fractions; 2) Add a certain amount of SBA-15 supported single basic component catalyst to the acidic component precursor solution obtained in step 1) and stir at 40-70℃ for 1-4 hours. 3) After filtering and washing the mixture obtained in step 2) several times, the resulting filter cake is placed in an oven at 80°C and dried for 12-48 hours; 4) The material obtained in step 3) is placed in a muffle furnace and calcined at 550°C for 3 hours at a rate of 2°C / min to obtain the SBA-15 supported acid-base synergistic catalyst.

4. The application of the SBA-15 supported acid-base synergistic catalyst according to claim 1, wherein the acid-base component loading of the catalyst is calculated based on the corresponding metal and the loading is 10-30 wt%.

5. The application according to claim 1, characterized in that: Using lactic acid as a raw material, at a mass hourly space velocity (H₂S) of 1–5 h₂S... -1 At a vaporization temperature of 140–160℃ and a reaction temperature of 210–250℃, lactic acid is catalyzed to convert to lactide.

Citation Information

Patent Citations

  • Method for preparing lactide by catalytic method under reduced pressure

    CN102675277A

  • Preparation method of medical lactide

    CN108424408A

  • Preparation method of lactide

    CN108610323A

  • Method for synthesizing lactide in one step

    CN112028869A

  • Preparation method and catalysis application of acidic-basic functionalized mesoporous material by using solid-state ionic migration method

    CN102091645A